Testing for Unit Roots in Nepalese Macroeconomic Data - Shrestha, Min Bahadur (NRB Economic Review, 2006)
Unit root test is viewed as mandatory on time series data since these data may possess specific properties like memory, trend and structural break. The results obtained by employing conventional regression methods without testing for the unit root in time series data might be misleading. This paper presents an overview of various unit root test methods and conducts the unit root test on Nepalese key macroeconomic data allowing one endogenous structural break. The test results show that out of the 18 macroeconomic variables, 10 have unit roots and the remaining 8 are stationary. An analysis of the structural break dates of these variables suggests that the Nepalese economy has gone through a structural change after mid-1980s.